Turning the table toward plant-based: different perspectives on menu reformulation in food service - Rocha, Ada; Viegas, Claudia; Gonçalves, Sara (Frontiers in Nutrition, 2025)
Scientific evidence supports the need to adapt food systems, counteracting the current scenario characterized by excessive and growing consumption of animal products that translates into high environmental impact, unsustainability, and negative effects on health. The food services are responsible for a high and increasing carbon footprint, emerging as a sector that promotes food sustainability through the adaptation of its operational processes and food supply. The main objective of this research was to evaluate the impact of menu reformulation and changes in the food offer on consumers’ perception and acceptance at a food service unit. A study with two stages was conducted using a convenience sample of canteen consumers (n = 55), and canteen employees (n = 6) to which a self-completion questionnaire was applied. Participants were mostly female (76.2%) and had a mean age of 40 ± 9.4 years. Menus were reformulated in stage one; stage two included food offer reformulation. Meat was considered the most important food group in both studies. Food and nutrition were highlighted as important to consumers (>80%) with statistically significant differences (p < 0.05). Most participants did not notice the changes made in the study (>55%). Only 32.4% of the participants were satisfied with the proposed changes, but approximately 65.8% were willing to keep the suggested changes in the future. The results of this study present clues and opportunities for strategies to change the food offer of the food service aiming to healthier and more sustainable meals.